Influencing factors in caretakers selection of food for children of early childhood education: bioethical analysis within in exploratory study - Azevedo Leung, Maria do Carmo; Doce Passadore, Mariana; Chemin Seabra da Silva, Sandra Maria (O Mundo da Saúde, 2016)
An ethical analysis is crucial for the role of the family in the development of eating habits of their children. This study covers a bioethical contextualization about the influence of advertisement in caretakers as to the purchase and selection of food offered for children of early childhood education. The study population was composed of 162 caretakers of children, enrolled in municipal schools of childhood education in 2013, and the data was collected by means of questionnaires sent in children’s agenda. Interviewees highlighted the healthiness of the food as decisive factor for the purchase of food (77.2%), whereas the media was reported as the minor influencing factor in the purchase of food (63%). This study demonstrates that caretakers do have concerns as to the choice of foods to be purchased and offered to children. The ethical aspects must always come ahead of economic and other secondary interests such as social status.